Biosafety : microbiological analysis of jackets of u niversity students of health courses - Pinto, Isabela Ribeiro (2017)
Health care students are in permanent contact and h andling with biological agents, and using jackets i n inappropriate environments and can contaminate clot hing, other students, the environment and the popul ation. The present study aimed to verify the contamination rat e of jackets of students investigating the situatio n of biosafety. The collect was held with sterile swab in the tissu es, in an area of approximately 4 cm 2 of the sleeves and of the front of the jackets of 100 students and the sample s were plated on Petri containing Blood Agar for mi crobiological analysis. Microbial contamination was detected in 85% of the jackets; being 78,84% Pharmacy students, 95% Nursing, 94,44% Dentistry and 80% Medicine. There w ere observed the presence of Gram-negative and Gram - positive cocci, bacilli, hemolytic bacteria. It con cludes that the jackets are contamination vectors, requiring awareness from the students to the practice of Bios afety.